The Effects of Clinical Pharmacist Education on Lifestyle Modifications of Postmyocardial Infarction Patients in South India: A Prospective Interventional Study - Sarumathy Sundararajan, M. Pharm; Shanmugarajan Thukani Sathanantham, M. Pharm., PhD; Shanmugasundaram Palani, M. Pharm., PhD (Elsevier, 2020)
ABSTRACT: Background: Myocardial infarction (MI) is associated with significant short-term and long-term mortality and morbidity. Secondary prevention and treatment of post-MI patients through medication and lifestyle modification is becoming an important aspect of patient care regimens. Pharmacists have a crucial role in providing these disease-prevention interventions compared with other health care professionals. Objectives: The primary objective included evaluation of clinical pharmacist interventions at discharge and post-MI discharge follow-up to improve the secondary lifestyle modifications and medication adherence among post-MI patients. The secondary objective included the prevention of hospital readmission rates for major adverse cardiovascular events and death among post-MI patients. Methods: In this prospective interventional study comprising 160 screened patients, 154 patients were randomized according to eligibility criteria of whom 77 were enrolled in Group A (the intervention group: clinical care along with pharmacist education) and 77 in Group B (the control group: clinical care with usual counseling) (November 2017-April 2018). Two patients were lost to follow-up in both study groups. Group A patients received clinical care with pharmacist structured intervention at post-MI discharge and through telephone follow-ups, whereas Group B patients received clinical care with usual counseling at baseline. Patients in both groups were analyzed for secondary lifestyle modifications such as fasting blood sugar level; postprandial blood sugar level; blood pressure; and total cholesterol, LDL-C, HDL-C, VLDL-C, and triglyceride level; hospital readmission rates; and medication adherence at the baseline. At the end of 6 months patients in both study groups underwent follow-up. Medication adherence was analyzed using the Medication Adherence Rating Scale. Statistical analysis was carried out by using SPSS software version 17 (SPSS-IBM Inc, Armonk, NY). Results: The mean (SD) age of the study population was 56.38 (11.68) years in Group A and 53.93 (13.26) years in Group B. Ther were more male patients than female patients in the study population. There was a statistically significant reduction in systolic and diastolic BP in Group A (P ˃ 0.0031 and P ˃ 0.0069, respectively) compared with Group B. Reduction in total cholesterol levels were observed in Group A compared with Group B (P ˃ 0.0001) patients, but there were no significant reductions found in lipid profile values, including LDL-C (P ˃ 0.0669), HDL-C (P ˃ 0.595), triglyceride (P ˃ 0.119), and VLDL-C (P ˃ 0.4215) at follow-up. Group A patients were more adherent to the medications with lower hospital readmission rates compared with Group B. Conclusions: Clinical pharmacist counseling improved the medication adherence and lifestyle modifications in post-MI patients with the reduction in blood glucose levels, blood pressure, and total cholesterol levels among the study population.